Association of ADRA2A and MTHFR gene polymorphisms with weight loss following antipsychotic switching to aripiprazole or ziprasidone - Roffeei, S.N.; Reynolds, G.P.; Zainal, N.Z.; Said, M.A.; Hatim, A.; Aida, S.A.; Mohamed, Z. (2014)
ObjectivesVarious genetic polymorphisms have been reported to be associated with antipsychotic-induced weight gain. In this study, we aimed to determine whether risk polymorphisms in 12 candidate genes are associated with reduction in body mass index (BMI) of patients following switching of antipsychotics to aripiprazole or ziprasidone. MethodsWe recruited 115 schizophrenia patients with metabolic abnormalities and who have been on at least 1year treatment with other antipsychotics; they were then switched to either aripiprazole or ziprasidone. They were genotyped, and their BMI monitored for 6months. ResultsSignificant associations with reduction in BMI at 6months following switching were found in two of these genes: with rs1800544 of the ADRA2A gene (CC+CG -0.321.41kg/m(2) vs GG -1.04 +/- 1.63kg/m(2), p=0.013) and with rs1801131 of the MTHFR gene (AA -0.36 +/- 1.53 vs AC+CC -1.07 +/- 1.53, p=0.015). ConclusionThe study data indicated that carriage of the ADRA2A rs1800544 GG genotype and the MTHFR rs1801131 C allele are associated with BMI reduction in this population following switching of antipsychotics to aripiprazole and ziprasidone. Copyright (c) 2013 John Wiley & Sons, Ltd.